Three new species of the deep-water genus Bathycadulus (Mollusca, Scaphopoda, Gadilidae) - Scarabino, Victor; Caetano, Carlos Henrique Soares; Carranza, Alvar (Zootaxa, 2011)
The genus Bathycadulus Scarabino, 1995 was described on the basis of a bathyal species (Bathycadulus fabrizioi Scarabino, 1995) collected from the southern Indian and western Pacific waters. Here we describe three new species, and conduct a morphometric analysis of shells of the four species. Those findings confirming the rather large bathyal and abyssal geographic distribution of the genus.